THE LEGAL STATUS OF THE SUBCONTRACTOR IN THE FIELD OF THE CONTRACTUAL GROUP - Hayder Awad Hammadi; Hakim Jubayr Hanun (Scholar Express Journals, 2021)
Under the contracting contract, the business contracts with a project worker to promise the last option to play out a specific work towards the first, however the worker for hire might allot this work to someone else to finish it or add to it, and subsequently the primary worker for hire contracts with the second worker for hire with another agreement whose gatherings are the principal worker for hire who recently contracted with The business, and the second project worker who is a (subcontractor), so we have two agreements, the first contracting contract, which is the main agreement between the principal project worker and the business, and a subcontracting contract between the primary project worker and the subsequent worker for hire (the subcontractor), and as per a relative standard The impact of the agreement, the sub-worker for hire is viewed as an outsider for the principal contract, so the sub-project worker can't request the business in his name to carry out his commitments forced on him by the main (unique) contracting contract. The issue of this examination lies in changing the legitimate status of the subcontractor, from being unique about the primary agreement (the first contracting contract) to someone else who plays a part in the execution of this agreement, even though he didn't take part in its decision, and that the chance of the subcontractor's intercession is conceivable based on The possibility of the nodal bunch that depends on the unit of the spot of agreements, that is, it depends on a progression of agreements wherein those agreements are supplanted by one, and along these lines the situation of the subcontractor changes from being a change from the agreement to a supporter of its execution, that is, he plays a part in the execution period of the agreement regardless of being He didn't add to its decision.
Keywords: Subcontractor; contract group; legal status; tort liability